Համաշխարհային գրական ժառանգությունը Հայաստանի ազգային գրադարանում - Հարությունյան, Արմինե («Գիրք» հրատ.)
The article includes information about the library’s digital collections and foreign literature in the UniArmenian catalogue. The information about collections on Armenian studies in foreign languages, supported and non-supported languages, and types of foreign language print materials available at the National Library of Armenia is presented. The article also discusses the value of foreign language literature and how in demand it is in Armenia, as well as the role and importance of foreign language Armenian press and what efforts are being done in that direction. A summary is provided on how much the National Library of Armenia has contributed to the replenishment of foreign language collections according to statistics of the last ten years, when the greatest number of foreign language literature was acquired, as well as what unique books are kept in the collection. The role and importance of press on Armenian studies in foreign languages and what efforts are being done in that direction also discussed.
Keywords: Համաշխարհային գրական ժառանգություն